Contrastive Conversation Analysis: Turn – Taking Strategies in Queen Rania Interviews - Prof. Dr. Qasim A. Dhayef; Fatima Selman (Zien Journals, 2022)
Conversation analysis (CA) is an approach to social research that investigates the sequential organisation of talk as a way of accessing participants' understandings of, and collaborative means of organising, natural forms of social interaction. A distinctive methodological feature is that CA gathers its data of naturally-occurring interactions as they unfold in real time using video- or audio-recording technology. Recordings are transcribed in close detail to allow for fine-grained analysis of the design, exchange and coordination of actions within social interaction. This chapter introduces the intellectual foundations and basic principles of CA; discusses its approach to understanding turn-taking systems; outlines its approach to data collection and transcription; illustrates its analytical procedures; and discusses the application of CA to institutional interaction and other sociological topics. (Atkinson, J. Maxwell and Heritage, John:1984). The present study tires to impact the turn taking strategies (in the selected data ) which occurs in a conversation when one person listens while the other person speaks. As a conversation progresses, the listener and speaker roles are exchanged back and forth (a circle of discussion). Queen Rania was born in Kuwait to Palestinian parents. She received her bachelor's degree in business at The American University in Cairo. In 1991, following the Gulf War, she and her family fled to Amman, Jordan, where she met Prince Abdullah of Jordan. (Hellomagazine.com). The present study tries to investigate the turn taking strategies in Queen Rania's interviews with Oprah Winfrey show and in Kalam Nwa'm Show.
Keywords: contrastive; turn taking; discourse particles; gaze direction